C‐Myc‐mediated epigenetic silencing of MicroRNA‐101 contributes to dysregulation of multiple pathways in hepatocellular carcinoma. Issue 5 (27th March 2014) - Wang, Lei; Zhang, Xiang; Jia, Lin‐Tao; Hu, Si‐Jun; Zhao, Jing; Yang, Jian‐Dong; Wen, Wei‐Hong; Wang, Zhe; Wang, Tao; Zhao, Jun; Wang, Rui‐An; Meng, Yan‐Ling; et al.
<x xml:space="preserve">Abstract</x> The MYC oncogene is overexpressed in hepatocellular carcinoma (HCC) and has been associated with widespread microRNA (miRNA) repression; however, the underlying mechanisms are largely unknown. Here, we report that the c‐Myc oncogenic transcription factor physically interacts with enhancer of zeste homolog 2 (EZH2), a core enzymatic unit of polycomb repressive complex 2 (PRC2). Furthermore, miR‐101, an important tumor‐suppressive miRNA in human hepatocarcinomas, is epigenetically repressed by PRC2 complex in a c‐Myc‐mediated manner. miR‐101, in turn, inhibits the expression of two subunits of PRC2 (EZH2 and EED), thus creating a double‐negative feedback loop that regulates the process of hepatocarcinogenesis. Restoration of miR‐101 expression suppresses multiple malignant phenotypes of HCC cells by coordinate repression of a cohort of oncogenes, including STMN1, JUNB, and CXCR7, and further increases expression of endogenous miR‐101 by inhibition of PRC2 activation. In addition, co‐overexpression of c‐Myc and EZH2 in HCC samples was closely associated with lower expression of miR‐101 (P < 0.0001) and poorer prognosis of HCC patients (P < 0.01). Conclusions: c‐Myc collaborates with EZH2‐containing PRC2 complex in silencing tumor‐suppressive miRNAs during hepatocarcinogenesis and provides promising therapeutic candidates for human HCC. (Hepatology 2014;59:1850–1863)